3D Atomic‐Scale Dynamics of Laser‐Light‐Induced Restructuring of Nanoparticles Unraveled by Electron Tomography. Issue 33 (11th July 2021) - Albrecht, Wiebke; Arslan Irmak, Ece; Altantzis, Thomas; Pedrazo‐Tardajos, Adrián; Skorikov, Alexander; Deng, Tian‐Song; van der Hoeven, Jessi E.S.; van Blaaderen, Alfons; Van Aert, Sandra; Bals, Sara
Abstract: Understanding light–matter interactions in nanomaterials is crucial for optoelectronic, photonic, and plasmonic applications. Specifically, metal nanoparticles (NPs) strongly interact with light and can undergo shape transformations, fragmentation and ablation upon (pulsed) laser excitation. Despite being vital for technological applications, experimental insight into the underlying atomistic processes is still lacking due to the complexity of such measurements. Herein, atomic resolution electron tomography is performed on the same mesoporous‐silica‐coated gold nanorod, before and after femtosecond laser irradiation, to assess the missing information. Combined with molecular dynamics (MD) simulations based on the experimentally determined 3D atomic‐scale morphology, the complex atomistic rearrangements, causing shape deformations and defect generation, are unraveled. These rearrangements are simultaneously driven by surface diffusion, facet restructuring, and strain formation, and are influenced by subtleties in the atomic distribution at the surface. Abstract : Atomic‐resolution electron tomography reveals atomic rearrangements in metal nanoparticles upon femtosecond laser excitation. Based on the measured 3D atomic structure, molecular dynamics simulations unravel the dynamics of the underlying process and give insight on how strain, crystal facet distribution, and surface diffusion govern these rearrangements.